Effectiveness of Statewide Advertising Campaigns in Promoting the QUITPLAN® Services Brand. (December 2013) - Lee, Jeong Kyu; Mowery, Andrea; Depue, Jacob; Luxenberg, Michael; Schillo, Barbara
The current study explored the role of advertising in building an effective cessation service brand in Minnesota, United States. Using data from a ClearWay Minnesota SM campaign evaluation ( N = 1, 361), this study examined how mass media advertising works to reinforce recognition of the QUITPLAN Services brand, brand favorability, and brand attributes. Respondents with confirmed awareness of television campaign ads were significantly more likely to report ever hearing of the brand than those who were not aware of the ads (odds ratio [OR] = 4.28, p < .001). In addition, confirmed ad awareness correlated with brand favorability (β = .37, p < .001) and attributes (personalized: β = .50, p < .001; respectful: β = .43, p < .001; proven: β = .42, p < .001; accessible: β = .46, p < .001), and there was a significant relationship between brand favorability and intention to quit among smokers (OR = 2.44, p = .001). The findings in this study contribute to the literature on social marketing and health branding by demonstrating effective strategies for establishing a cessation service brand. Practical implications, research limitations, and future directions are discussed.